Hypothermic treatment for neonatal asphyxia in low‐resource settings using phase‐changing material—An easy to use and low‐cost method. (12th May 2020) - Tran, Hang T. T.; Le, Ha T. T.; Tran, Hanh T. P.; Khu, Dung T. K.; Lagercrantz, Hugo; Tran, Dien M.; Winbladh, Birger; Hellström‐Westas, Lena; Alfvén, Tobias; Olson, Linus
Abstract: Aim: To evaluate whether phase‐changing material can be used for therapeutic hypothermia of asphyxiated newborns in low‐resource settings. Methods: Prospective interventional study of asphyxiated term infants fulfilling criteria for hypothermia treatment at Vietnam National Children's Hospital from September 2014 to September 2016. Hypothermia was induced within 6 hours after birth and maintained for 72 hours by a phase‐changing material mattress with melting point of 32°C. Rectal temperature was continuously measured, and deviations from target temperature range 33.5‐34.5°C were recorded. Results: In total 52 infants (mean gestational age 39.3 ± 1.1 weeks) included and cooled, the median temperature at initiation of cooling was 35.3 (IQR 34.5‐35.9)°C. The median time to reach target temperature was 2.5 (IQR 2‐3) hours. The mean temperature during the cooling phase was 33.95 ± 0.2°C. Throughout the cooling phase, the target temperature range (33.5‐34.5°C) was maintained more than 80% of the time. Rate of rewarming was 0.5 ± 0.14°C/hour. Conclusion: Phase‐changing material can be used as an effective cooling method. Though not a servo‐controlled system, it is easy to induce hypothermia, maintain target temperature and rewarm infants in a slow and controlled manner without need for frequent changes and minimum risk of skin injury.